1997
DOI: 10.1002/(sici)1097-4636(19970615)35:4<483::aid-jbm8>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of specific calcium-binding noncollagenous proteins associated with glutaraldehyde-preserved bovine pericardium in the rat subdermal model

Abstract: Calcification of glutaraldehyde-preserved bioprosthetic heart valves (BHVs) results in their clinical failure. The mechanism of this pathologic calcification is not well defined. Since serum proteins are known to be taken up in mineralized tissue, we hypothesized that serum proteins derived from several calcium-binding noncollagenous proteins (NCPs) of bone and teeth also may be associated with pathologically mineralized BHVs. Using a rat subdermal model of BHV calcification, glutaraldehyde-preserved bovine pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Several findings do, however, point to a cellular function. Gura et al (1997) found non-collagenous proteins tightly bound to the mineral phase in subdermal implants of glutaraldehyde-preserved bovine pericardium with marked accumulation of highly acidic, phosphorylated proteins; they reported that ON increased within three days after implantation but its duration decreased by two weeks, and that BAG-75 and OPN uptake could be detected in initial inorganic deposits and increased with calcification. Levy et al (1980) have detected OC in three calcified porcine xenograft valves and in a calcified homograft valve.…”
Section: Calcification Of Implanted Cardiac Bioprosthetic Valvesmentioning
confidence: 99%
“…Several findings do, however, point to a cellular function. Gura et al (1997) found non-collagenous proteins tightly bound to the mineral phase in subdermal implants of glutaraldehyde-preserved bovine pericardium with marked accumulation of highly acidic, phosphorylated proteins; they reported that ON increased within three days after implantation but its duration decreased by two weeks, and that BAG-75 and OPN uptake could be detected in initial inorganic deposits and increased with calcification. Levy et al (1980) have detected OC in three calcified porcine xenograft valves and in a calcified homograft valve.…”
Section: Calcification Of Implanted Cardiac Bioprosthetic Valvesmentioning
confidence: 99%
“…PGs and GAGs were extracted in 4 m guanidine HCl in sodium acetate, pH 5.8, containing protease inhibitors: 1 mm p-hydroxymercuribenzoate, 1 mm phenylmethylsulfonyl fluoride, 1 mg/ml soybean trypsin inhibitor and 10 mm EDTA [22]. After dialysis (MWCO 12,000) at 4 C for 72 h against distilled water, the PG/GAGs content of the extracted samples was determined with a Blyscan assay kit (Biocolor Ltd., Belfast, North Ireland) and expressed as micrograms per milligram of wet weight tissue.…”
Section: Proteoglycan/glycosaminoglycan Extraction and Quantificationmentioning
confidence: 99%
“…Pathologic calcifications in soft tissue, similar to those present in calcified heart valves (1), are a complication of several connective tissue diseases, increasing morbidity and mortality (2, 3). In contrast to adults with dermatomyositis (DM), in whom calcification is relatively uncommon, it is estimated that 20–40% of children with juvenile DM have calcific deposits (3).…”
mentioning
confidence: 99%